Manual Aid in the Vaginal Delivery of Spontaneous Twin Cephalic-Complete Breech Pregnancy: A Case Report - Nanda R.P, Gustie; Sujatmiko, Tejo; G.T, Kanesti Ismirajna; Riana, Salsabila (Jurnal Health Sains, 2025)
Multiple gestation, particularly those involving a combination of breech and cephalic presentations, presents a complex obstetric challenge. This case report describes the successful vaginal delivery of a twin pregnancy with mixed presentation at 36/37 weeks of gestation. A 28-year-old woman, G2P1A0, presented in active labor with a cervical dilation of 4 cm. The first twin was in cephalic presentation, while the second was in breech. Following the NICE guidelines for twin delivery with a cephalic-presenting first twin, a vaginal delivery was planned. The first baby was delivered spontaneously. For the second, breech-presenting twin, an amniotomy was performed, followed by a Manual Aid for Breech Delivery, resulting in a safe vaginal birth. Both infants had satisfactory Apgar scores, and the third stage was managed without significant postpartum haemorrhage. This case demonstrates that with careful monitoring and skilled intervention, vaginal delivery is a viable and safe option for twin pregnancies with a cephalic-breech combination, potentially avoiding the need for cesarean section. The successful outcome underscores the importance of preparedness for breech extraction and holistic management during the intrapartum and postpartum periods.